Reproduction methods and bioproductivity of Maclea x kevensis Turill in the Western Caucasus - O. A. Bykova; N. I. Sidelnikov; R. N. Thaganov; V. R. Thaganov (Овощи России)
At present, much attention is paid to medicinal plants, the raw material of which is used for the production of drugs with antibacterial activity. Such plants include Macleaea x kevensis Turill. Due to the fact that this crop does not grow under natural conditions in the Russian Federation, there is a question of creating industrial plantations of Macleau x kevensis Turill. To solve this problem, it is necessary to determine a promising way of propagation of the plant and develop a balanced use of mineral fertilizers in order to obtain maximum yields of high quality medicinal raw materials. The research was carried out on the experimental fields of medicinal crop rotation of the North Caucasus branch of FGBNU VILAR, located in the Western Caucasus, in order to study the ways of multiplication of the crop and the timing of its planting. Field experiments were laid by setting up experiments with small area. Phenological observations were carried out, peculiarities of growth and development of plants were studied, yield and content of active substances were determined. The conducted researches have established that the most effective way of propagation of Macleau x kevensis Turill in the conditions of Western Ciscaucasia is autumn planting by cuttings of rhizomes 10-15 cm long. With this method of multiplication of the culture, its ear- lier regrowth in the spring, active growth and development of plants are observed. It allows to harvest the raw material already in the first year of vegetation and provides the yield of medical raw material of Macleau x kevensis Turill at the level of 1,12 t/ha and the alkaloid content 1,02%. If we applied foliar top dressing NPK45, then in I-III years of vegetation of the crop, the yield of raw materials increased by 25-27% and the content of alkaloids increased by 6-9%, and their yield per hectare – by 30-38%.